ATOMIC ABSORPTION AND ATOMIC EMISSION SPECTROMETRY FOR THE MICRO-DETERMINATION OF METFORMIN EMPLOYED IN CONTROL OF BLOOD SUGAR LEVEL IN PHARMACEUTICAL FORMULATIONS AND URINE SAMPLES - S.KHALIL,; Y. M. HUSSEIN,; A. BUSHARA,; B. RAAFAT, (International Journal of Pharma and Bio Sciences, 2015)
Ion-associate complexes of metformin hydrochloride drug employed in control of blood sugar level with ( manganese(II), zinc(II) and cadmium(II)) thiocyanates and ammonium reineckate are precipitated. The solubility of the solid complexes at the recommended optimum conditions of pH and ionic strength values have been studied. Saturated solutions of each ion associate at different temperatures under the optimum precipitation conditions were prepared and the metal ion contents in the supernatant were determined. A new accurate and precise method based on direct coupled plasma atomic emission and atomic absorption spectrometry for the determination of metformin (0.33-36.42 μg/ml) in pure solution, pharmaceutical Formulations and in urine samples of diabetic patients type-2 in Taif Area, Saudia Arabia is given.